Science Teachers Competencies and Problem in Implementing 2013 Curriculum at Primary and Secondary School in Bali - Anak Agung Inten Paraniti; Ketut Suma (Universitas Pendidikan Ganesha, 2022)
Teachers are the key to success in implementing the curriculum; however, many studies report problems implementing the K-13 curriculum, including teachers' competencies. There has been no thorough report on teacher competence related to issues in the implementation. This study examines science teacher competencies in three main aspects, namely skill to design, manage and implement learning in the K-13 curriculum. Mix method was used in this study with a concurrent mixed method design. First, the survey involved 67 respondents who filled out a science teacher competencies questionnaire based on the process standards of the K-13 curriculum. Meanwhile, the qualitative part was conducted by conducting structured interviews with 12 science teachers about challenges and problems related to three main aspects of science teacher competencies in implementing the k-13 curriculum. Quantitative data in percentages is collected, while qualitative data analysis is done through data reduction, presentation, and verification. The competence of teachers in learning design must be further improved in creativity and goal setting to match the allocation of time, activities, dan learning assessments in the process of making learning plans. Science teachers' competence should be improved in arranging the seats according to the goal and characteristics of education. The competence of implementation must be further improved in two indicators: the creativity of learning implementation, which is in line with the teacher's understanding of various innovative learning models, and learning implementation, in line with the lesson plan.